2016
DOI: 10.1186/s12966-016-0437-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of frequent interruptions of prolonged sitting on self-perceived levels of energy, mood, food cravings and cognitive function

Abstract: BackgroundWhile physical activity has been shown to improve cognitive performance and well-being, office workers are essentially sedentary. We compared the effects of physical activity performed as (i) one bout in the morning or (ii) as microbouts spread out across the day to (iii) a day spent sitting, on mood and energy levels and cognitive function.MethodsIn a randomized crossover trial, 30 sedentary adults completed each of three conditions: 6 h of uninterrupted sitting (SIT), SIT plus 30 min of moderate-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
82
2
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(109 citation statements)
references
References 36 publications
7
82
2
4
Order By: Relevance
“…Besides, skeletal muscle activity has long been associated with increased epinephrine secretion (Kjaer, Christensen, Sonne, Richter, & Galbo, ). Bergouignan, Legget, De Jong, et al () reported that urinary epinephrine concentration increased from 6.5 μg/g to 8.0 μg/g in individuals performing microbouts of 5‐minute moderate walking to break sedentary time when compared with sedentary individuals. Although statistical significance was not reached, epinephrine concentration was not the primary outcome of the trial, which may indicate that the secretion of this hormone increase with reduced sitting time.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, skeletal muscle activity has long been associated with increased epinephrine secretion (Kjaer, Christensen, Sonne, Richter, & Galbo, ). Bergouignan, Legget, De Jong, et al () reported that urinary epinephrine concentration increased from 6.5 μg/g to 8.0 μg/g in individuals performing microbouts of 5‐minute moderate walking to break sedentary time when compared with sedentary individuals. Although statistical significance was not reached, epinephrine concentration was not the primary outcome of the trial, which may indicate that the secretion of this hormone increase with reduced sitting time.…”
Section: Discussionmentioning
confidence: 99%
“…In total, 622 participants took part (229 males, 311 females, 82 unidentified). One study was a RCT [35], one study was of a non-randomized parallel group design [36] and 20 studies were CO in design [37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56]. Seven studies evaluated a cycling intervention, 13 studies evaluated a walking intervention and two studies evaluated both types of intervention (see Supplementary File 2).…”
Section: Literature Search and Study Characteristicsmentioning
confidence: 99%
“…The heart rate measured during worktime in the studies varied from 77 to 110.6 bpm in the intervention group and from 71 to 82 bpm in the control group. Studies evaluating the daily heart rate [38,46] observed a mean value of 78-80 bpm in the intervention group and 70-72 bpm in the control group. The pooled effect size showed a significant increase in heart rate (SMD = 1.68, 95% CI [1.13, 2.23], p < 0.001, I 2 = 91%) in the intervention group.…”
Section: The Effects Of Interventions On Cardiovascular Indicatorsmentioning
confidence: 99%
“…For instance, sedentary behavior [9,10] and physical inactivity [11,12] are associated with worsened cognitive functions and a higher risk of neurodegenerative diseases (e.g., dementia) in the aging population [13][14][15][16][17][18][19][20][21][22]. In order to avoid periods of prolonged physical inactivity and sedentary behavior (e.g., sedentism during office working day), it is advised to take physical activity breaks ( [23][24][25]. There is substantial evidence in the literature showing that acute (single) bouts of physical exercise (defined as planned and structured form of distinct physical activities [26][27][28][29]) Figure 1.…”
Section: Introductionmentioning
confidence: 99%